Pengaruh Penyiraman Air Cucian Beras Fermentasi Satu Hari Dan Fermentasi Lima Belas Hari Terhadap Kadar Pigmen Fotosintetik Dan Pertumbuhan Vegetatif Tanaman Sawi Hijau (Brassica juncea L.) - Fadilah, Aprilia Nurul; Darmanti, Sri; Haryanti, Sri (Bioma : Berkala Ilmiah Biologi, 2020)
Mustard plants are a type of vegetable favored by most people. Demand formustard plants continues to increase along with the increasing population and awareness of nutritional needs, but there are obstacles in increasing the production. This is due to the lack of nutrients needed by the mustard plant for its growth. One effort to increase the production of mustard plants is by adding nutrients through fertilization. Fertilizers are divided into two types, namely organic and inorganic fertilizers. However, long-term use of inorganic fertilizers can reduce soil quality and environmental health. One alternative to overcome these problems is to use liquid organic fertilizer in the form of fermented rice washing water. This study aims to determine the effect of 1-day fermented rice washing water and 15-days fermented rice washing water at different concentrations on photosynthetic pigment content and vegetative growth of green mustard plants and find out the best dose of rice washing water for the growth of green mustard plants. The study used a Completely Randomized Design (CRD) of 1 factor with 5 treatments. Each treatment with 4 replications with ordinary water as a control, 1-day fermented rice washing water with the concentration of 50% and 100%, and 15-days of fermented rice washing water with the concentration of 50%, and 100%. The results showed that the watering on 1-day fermented rice washing water with the concentration of 50% and 100% and 15-days of fermented rice washing water with a concentration of 50% had no effect on all parameters but the watering of 15-days fermented rice washing water with a concentration of 100% had an effect on increasing the plant height, number of leaves, leaf area, plant fresh weight, and plant dry weight. The growth of mustard green plants (Brassica juncea L) is best obtained in the treatment of 15-days fermented rice washing water with a concentration of 100%.